Oralidade como objeto de ensino: um estudo sobre o uso público do oral em contextos escolar e extraescolar - Tainá Nínive Soares Guerra de Oliveira (2017)
Through this research, it has been verified how High School students are able to learn and understand the necessary adjustments in the use of oral expression in situations of public use of the language and also the extent to which systematized activities in an intervention project may contribute to increase their language skills. In addition, it has been sought to understand to what extent out-of-school contact with orality influences oral production in work exhibitions within the classroom. The hypothesis is that the student who often employs the public uses of oral language out of school becomes more competent in using it in the classroom. The research sought support in authors such as Kleiman (2007), Dolz, Noverraz and Schneuwly (2004), Guimarães & Kersh (2014), as well as Cristóvão & Stutz, (2011). It is an applied qualitative research, since it has intended to analyze teaching practices in order to understand the results obtained through the teaching/learning process with high school students. However, it also contains some quantitative data that helped highlight important points for the analysis of pedagogical practice. The research analyzes activities through which teachers can instruct the production of oral genres with public use in order to mobilize varied language abilities, based on Dolz & Schneuwly (2004), Cristóvão & Stutz (2011), and make the students able to produce oral texts, being aware of the requirements and adaptations to different situations of communication. The data show that the out-of-school groups surveyed, in which students often have contact with oral language, exert a relevant influence on the students oral performance in the classroom. The results also evidence that the systematic teaching of oral expression, when guided by the social practice of the student, promotes a significant advance in his/her production, making them mobilize language skills in a balanced way.